12q-6=8q+14

Simple and best practice solution for 12q-6=8q+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12q-6=8q+14 equation:


Simplifying
12q + -6 = 8q + 14

Reorder the terms:
-6 + 12q = 8q + 14

Reorder the terms:
-6 + 12q = 14 + 8q

Solving
-6 + 12q = 14 + 8q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-8q' to each side of the equation.
-6 + 12q + -8q = 14 + 8q + -8q

Combine like terms: 12q + -8q = 4q
-6 + 4q = 14 + 8q + -8q

Combine like terms: 8q + -8q = 0
-6 + 4q = 14 + 0
-6 + 4q = 14

Add '6' to each side of the equation.
-6 + 6 + 4q = 14 + 6

Combine like terms: -6 + 6 = 0
0 + 4q = 14 + 6
4q = 14 + 6

Combine like terms: 14 + 6 = 20
4q = 20

Divide each side by '4'.
q = 5

Simplifying
q = 5

See similar equations:

| [40x^22y^11/20x^11y^22]^2 | | 2x+3+5x=-9-4x+2x | | 14-1/6n=1/6n-1 | | 2.7=2n-4 | | -0.5x+0.9x=51 | | 16-n=5(n)+4 | | g(5)=64(0.5(5)) | | 19=3c+1 | | 8x-6-2x=10+4x | | x^3-x^2-x+20=0 | | 7.1=2.6-0.7y | | 7x-30=5x-14 | | 10x-3=8x+16 | | 3w-3(w-5)=22 | | 7x-30=5x-15 | | 1+8(n)=12(n)-15 | | 7x+4=x+1 | | 5x+16-9x=18-13x+9x-2 | | -2p-3(5-2p)=2(p-4)-17 | | 2/5=13/x | | 4(n)=12-2n | | -3x*x+6x=-1 | | 7x-30=5x-21 | | -4a-2a=-7+a | | -9b+7=2 | | 4w(w-3)=0 | | X+6=-2x-6 | | 2(2y-7)=3y+4 | | tan49=7/x | | (3y-20)(y+10)70=180 | | 10/87=x/100 | | s(n)=(1/4)n |

Equations solver categories